Structural Paradigms in the Recognition of the Nucleosome Core Particle by Histone Lysine Methyltransferases - Janna, Ashley; Davarinejad, Hossein; Joshi, Monika; Couture, Jean-Francois (Frontiers in Cell and Developmental Biology, 2020)
The post-translational modifications (PTMs) of histone proteins play essential functions in shaping the chromatin environment. Alone or in combination, these PTMs create templates recognized by dedicated proteins or change the chemistry of chromatin, enabling a myriad of nuclear processes to occur. Referred to as cross-talk, the positive or negative impact of a PTM on another post-translational modification has rapidly emerged as a mechanism controlling nuclear transactions. One of those includes the stimulatory functions of histone H2B ubiquitylation on the methylation of histone H3 on K79 and K4 by Dot1L and COMPASS, respectively. While these findings were established early on, the structural determinants underlying the positive impact of H2B ubiquitylation on H3K79 and H3K4 methylation were resolved only recently. We will review the molecular features controlling these cross-talks and the impact of H3K27 tri-methylation on EZH2, when embedded in the PRC complex, activity.